Andenes and late settlements in Caraybamba, Apurimac - Van Dalen Luna, Pieter (2009)
Caraybamba is a town in Apurimac that keeps alive many ancient cultural traditions. The investigations have revelated a long cultural occupation with Aymaraes influences at the top of the mountains that dated back to the Late Intermedium. The later invasion of Tahuantinsuyo implies the improvement of the andenes and the construction of new places like Allaqmarca and Wishkashuta with administrative control purposes.